Change of anti-Mullerian-hormone levels during follicular phase in PCOS patients. (January 2015) - Köninger, A.; Koch, L.; Enekwe, A.; Birdir, C.; Kasimir-Bauer, S.; Kimmig, R.; Strowitzki, T.; Schmidt, B.
Abstract Anti-Mullerian-hormone (AMH) does not seem to fluctuate significantly during the menstrual cycle in healthy women. However, little is known about cycle fluctuations of AMH levels in patients with polycystic ovarian syndrome (PCOS). The purpose of this study was to examine AMH fluctuations during the follicular phase in PCOS patients receiving antiestrogens or recombinant follicle-stimulating hormone (FSH). About 40 PCOS patients diagnosed according to Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group 2003 and 19 controls were prospectively enrolled. PCOS patients received either antiestrogens or recombinant FSH for monoovulation induction and controls received antiestrogens. AMH levels were determined (1) between the 2nd and the 5th day of follicular phase and (2) when a single large dominant follicle ≥18 mm had appeared. Our study shows that AMH levels do not change during follicular development in controls as well as in PCOS patients with AMH levels < 5 ng/ml, irrespective of antiestrogen or FSH therapy. However, in PCOS patients with AMH levels ≥5 ng/ml, AMH declines significantly during follicular development (p < 0.01). We conclude that AMH levels should be determined in the early follicular phase in PCOS patients without the influence of antiestrogens or exogenous FSH, because these interventions may lower AMH values in patients with high levels.